Usefulness of serum osteopontin level as a noninvasive parameter of portal hypertension - Ayman M Fouad; Nagwa Ramadan; Iman A.E Shaheen; Mohammed A Ismael (SpringerOpen, 2019)
Background Osteopontin (OPN) is a multifunctional protein that is physiologically expressed in the kidney and bone. Plasma OPN levels were shown to predict liver fibrosis in various chronic liver diseases and could be related to the degree of portal hypertension. The aim of the study is to investigate the usefulness of OPN as a noninvasive biomarker of portal hypertension. Patients and methods A case-control study including 90 (45 patients with confirmed liver cirrhosis and 45 normal healthy individuals) patients were enrolled in the study. Laboratory investigations with abdominal ultrasound and duplex of the portal system were carried out for all patients. OPN was measured using the enzyme-linked immunosorbent assay in the plasma. Results Compared with controls, the plasma levels of OPN in cirrhotic patients were significantly high (P<0.001). Also, plasma levels of OPN were significantly high in patients with portal hypertension (P<0.001). The cutoff value of OPN to detect the presence of portal hypertension is 1.65 ng/ml with sensitivity and specificity of 80 and 95.6%, respectively). Conclusion Serum OPN is a good noninvasive parameter to detect portal hypertension.